The Map of the Understanding Level of Cash Waqf for Jama'ah of Masjid in District of Ponorogo City - Abdul Latif; Imam Haryadi; Adib Susilo (Journal of Finance and Islamic Banking, 2021)
The low level of participation of waqf in society is caused by the low level of understanding of waqf. Therefore, this research is aimed to mapping the understanding of waqf. The object of the study is the mosque congregation in the district of Ponorogo. The method used in this study is qualitative descriptive with a corresponding approach. The data collected through interviews. The result of this study shows that the understanding of waqf is mapped on three themes namely, a basic understanding of waqf, an understanding of waqf benefits, understanding of the law related to waqf. This research also found that the level of understanding waqf based on the map is at a medium-low level. Means, the mosque congregation at the district of Ponrogo are still unfamiliar with waqf in term advanced understanding.